Studi Komparatif Implementasi Pembelajaran Berpusat Murid pada Sekolah Islam Terpadu di Tiga Jenjang Pendidikan - Salma Samputri; Rifda Nur Hikmahwati Arif (JAMBURA Elementary Education Journal, 2026)
This study compares the implementation of student-centered learning in three integrated Islamic schools in South Sulawesi: SD IT Yafat Baji Areng, SMPIT Al Hikmah Amanah Ummah Maros, and SMAIT Al Qalam Gowa Boarding School. A qualitative comparative case study design was used based on National Assessment visitation documents produced by the same assessor. The data were analyzed descriptively and thematically across 37 indicators. The results show that SMAIT Al Qalam Gowa achieved the highest performance, with 62.2% of indicators categorized as Very Good and 35.1% as Good. SMPIT Al Hikmah Amanah Ummah obtained 21.6% Very Good and 78.4% Good, while SD IT Yafat Baji Areng obtained 75.7% Good and 24.3% Fairly Good. Organizational maturity, resources, student developmental characteristics, and policy consistency are the main differentiating factors. Inclusive education, formative assessment, school safety, and health services still require strengthening.